2020
DOI: 10.1186/s12881-020-01001-5
|View full text |Cite
|
Sign up to set email alerts
|

New genetic variant in the SERPINC1 gene: hereditary Antithrombin deficiency case report, familial thrombosis and considerations on genetic counseling

Abstract: Background: Inherited deficiency of the antithrombin (hereditary antithrombin deficiency, AT deficiency, OMIM #613118) is a relatively rare (1:2000-3000) autosomal-dominant disorder with high risk of venous thromboembolism. Mutations in the serpin family C member 1 gene (SERPINC1) can lead to Quantitative (type I) and Qualitative (type II) types of antithrombin deficiency. We describe a new genetic variant in the SERPINC1 gene and our approach to variant interpretation. Case presentation: We observed a 29 y.o.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…As outlined in the previous section, tumor cell heterogeneity and especially the existence of CSCs in tumors is a major problem in the failure of cancer treatment. Since µ g delivers an exceptional environment for cell culture and has been shown to stimulate cellular changes and processes that could not be achieved under normal gravitational conditions [ 59 ], the investigation of how CSCs act under µ g is an interesting topic. Even though, to our knowledge, the number of published studies on CSCs exposed to µ g conditions is limited, researchers have initiated work in this essential field during recent years [ 59 , 60 ].…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
See 2 more Smart Citations
“…As outlined in the previous section, tumor cell heterogeneity and especially the existence of CSCs in tumors is a major problem in the failure of cancer treatment. Since µ g delivers an exceptional environment for cell culture and has been shown to stimulate cellular changes and processes that could not be achieved under normal gravitational conditions [ 59 ], the investigation of how CSCs act under µ g is an interesting topic. Even though, to our knowledge, the number of published studies on CSCs exposed to µ g conditions is limited, researchers have initiated work in this essential field during recent years [ 59 , 60 ].…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
“…Since µ g delivers an exceptional environment for cell culture and has been shown to stimulate cellular changes and processes that could not be achieved under normal gravitational conditions [ 59 ], the investigation of how CSCs act under µ g is an interesting topic. Even though, to our knowledge, the number of published studies on CSCs exposed to µ g conditions is limited, researchers have initiated work in this essential field during recent years [ 59 , 60 ]. Most knowledge has been obtained from thyroid, breast, and prostate cancer cells studies.…”
Section: Cancer Research In Microgravitymentioning
confidence: 99%
See 1 more Smart Citation
“…In high-risk settings, the use of AT replacement therapy reduces this risk [ 85 ]. Paradoxically, according to guidelines issued in 2012 by the American College of Chest Physicians, special antithrombotic agents should not be used prophylactically in women with a history of hereditary thrombophilia and pregnancy complications (grade 2C) [ 86 ]. Low-molecular-weight heparin (LMWH) has been widely recognized in the literature as a safe and effective alternative to oral anticoagulant therapy (e.g., warfarin) in early and late pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have found that antithrombin deficiency plays an important role in the pathogenesis of VTE. Antithrombin is an important inhibitor of blood coagulation proteases; individuals with hereditary AT deficiency have elevated thrombotic risk (29)(30)(31). Studies have revealed that the mutation profile of the AT gene (SERPINC1) is heterogeneous (32)(33)(34)(35).…”
Section: Introductionmentioning
confidence: 99%